2020
DOI: 10.1093/ibd/izaa011
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Virtual-based Chromoendoscopy Compared With Dye-spraying Chromoendoscopy Standard and High-definition White Light Endoscopy in Patients With Inflammatory Bowel Disease at Increased Risk of Colon Cancer

Abstract: Background Patients with inflammatory bowel disease (IBD) have an increased risk of colorectal cancer. We sought to assess the comparative efficacy of virtual chromoendoscopy (VCE) vs high definition white light endoscopy (HDWLE) or dye-spraying chromoendoscopy (DCE) through a meta-analysis and rating the quality of evidence. Methods A systematic review of the literature was performed through February 15, 2019. Primary outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 28 publications
0
42
0
Order By: Relevance
“…35 Early studies generally failed to show a benefit of VCE technologies for dysplasia detection with either standarddefinition or HD endoscopes in patients with cIBD. [36][37][38][39][40][41] However, several recent studies have shown similar dysplasia detection rates when comparing HD NBI with DCE 39,42,43 or HD iscan with DCE, 36,39 with shorter withdrawal times favoring VCE methods. A recent meta-analysis of 11 RCTs confirmed that VCE performed similarly to DCE and HD-WLE with respect to dysplasia detection on a perpatient basis.…”
Section: Adjuncts To Enhance Dysplasia Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Early studies generally failed to show a benefit of VCE technologies for dysplasia detection with either standarddefinition or HD endoscopes in patients with cIBD. [36][37][38][39][40][41] However, several recent studies have shown similar dysplasia detection rates when comparing HD NBI with DCE 39,42,43 or HD iscan with DCE, 36,39 with shorter withdrawal times favoring VCE methods. A recent meta-analysis of 11 RCTs confirmed that VCE performed similarly to DCE and HD-WLE with respect to dysplasia detection on a perpatient basis.…”
Section: Adjuncts To Enhance Dysplasia Detectionmentioning
confidence: 99%
“…A recent meta-analysis of 11 RCTs confirmed that VCE performed similarly to DCE and HD-WLE with respect to dysplasia detection on a perpatient basis. 39 Best Practice Advice 8: Extensive nontargeted biopsies (roughly 4 adequately spaced biopsies every 10 cm) should be taken from flat colorectal mucosa in areas previously affected by colitis when white light endoscopy is used without dye spray chromoendoscopy or virtual chromoendoscopy. Additional biopsies should be taken from areas of prior dysplasia or poor mucosal visibility.…”
Section: Adjuncts To Enhance Dysplasia Detectionmentioning
confidence: 99%
“…This is also reflected in their preference of surveillance modality, in which HDWLE with VCE ranked second. A recent meta‐analysis 32 revealed that virtual‐based chromoendoscopy was as good as HDWLE and dye‐spraying chromoendoscopy in identifying dysplasia per patient analysis. In addition, with the advantages of a shorter procedure time and overall the lower cost of the procedure resulting from avoiding methylene blue or indigo carmine and performing biopsies, VCE may assume a more important role in CRC surveillance in IBD in the future.…”
Section: Discussionmentioning
confidence: 99%
“…When looking at per patient analysis, there were no statistical differences between VCE, traditional chromoendoscopy, and HD-WLE. 26 Although still being investigated, VCE could be an additional modality that could be used by AI systems to target dysplasia in IBD.…”
Section: Dysplasia Detectionmentioning
confidence: 99%